Asthma in Tunisian elite athletes - Sallaoui, R.; Chamari, K.; Chtara, M.; Alaranta, A.; Manai, Y.; Ghedira, H.; Amri, M. (International Journal of Sports Medicine, 2007)
Several studies in the past few decades have shown that very intense and repeated exercise, particularly when performed over many years, could cause respiratory health problems. The prevalence of exercise-induced asthma has increased in the athletic population, particularly in elite athletes and has not been published in North African athletes. The aim of this study was to determine the prevalence of exercise-induced asthma and/or exercise-induced bronchoconstriction in Tunisian elite athletes. Each participant responded to a questionnaire about respiratory symptoms and medical history and underwent a resting spirometry testing before exercise. Exercise-induced bronchoconstriction was defined as a decrease of at least 15 % in pre-exercise forced expiratory volume in one second at any time point after exercise. Post-exercise spirometry revealed the presence of exercise induced bronchoconstriction in 14 out of 107 (13 %) elite athletes, while only 1.8 % of the subjects reported having previously diagnosed asthma. The prevalence of exercise-induced bronchoconstriction was 19 % (8/42) among those athletes training outdoors and 10 % (6/65) among those training indoors. In conclusion, our findings indicate that a significant number of Tunisian athletes had exercise-induced bronchoconstriction while not diagnosed before.